Milli-Joule pulses post-compressed from 14 ps to 475 fs in bulk-material multi-pass cell based on cylindrical vector beam - Zhang, Xu; Wang, Zhaohua; Wang, Xianzhi; Li, Jiawen; Li, Jiajun; Zhao, Guodong; Wei, Zhiyi (Chinese physics B, 2023)
A cylindrical vector beam is utilized to enhance the energy scale of the pulse post-compressed in a bulk-material Herriott multi-pass cell (MPC). The method proposed here enables, for the first time to the best of our knowledge, pulse compression from 14 ps down to 475 fs with throughput energy beyond 1 mJ, corresponding to a compression ratio of 30, which is the highest pulse energy and compression ratio in single-stage bulk-material MPCs. Furthermore, we demonstrate the characteristic of the vector polarization beam is preserved in the MPC.